Consumer motives for purchasing counterfeit luxury products: Behind the status signaling behavior using brand prominence - Pur Purwanto; Lulus Margiati; K. Kuswandi; Budi Prasetyo (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
The present study sought to describe the relationship of customer motives with counterfeit products and brand prominence and purchasing behavior in three groups/classes of consumers ( patrician , parvenus and poseur ) in the context of luxury brand fashion. Data were obtained from a sample consisting of 400 consumers considered eligible. There were three findings; first, for the poseur class, consumer motives for purchasing products had an effect on counterfeit products and conspicuous brand prominence, as well as purchasing behavior. Second, for the parvenus class, consumer motives for purchasing products had no significant effect on counterfeit products, but it had a significant effect on brand prominence and purchasing behavior. Third, for the patrician class, consumer motives for purchasing products had no significant effect on counterfeit products and conspicuous brand prominence, and counterfeit products and brand prominence had no significant effect on purchasing behavior.
Keywords: M3; M31; M39; 650; consumer motives; brand prominence; counterfeit products; purchasing behavior